PENGARUH RADIASI SINAR GAMMA TERHADAP PERTUMBUHAN DAN PERUBAHAN FENOTIPE TUNAS IN VITRO LIDAH BUAYA (ALOE VERA) - M Imelda; S Sari; A Wulansari; F Eriyandri (Jurnal Teknologi Lingkungan, 2011)
Aloe vera (L.) Burm.f. of the Asphodelaceae, which probably originated in North Africa is a very short-stemmed succulent, perennial plant of 80-100 cm in height. Today, it is widely grown in the tropics worldwide. It has long been used as a traditional herbal medicine and as cosmetic materials since thousand of years BC in Egypt, China, Greece, etc. It can be used externally to treat various skin conditions and It was useful for curing diabetics, cancer, HIV, even for stress and drug addicts The biologically active components found in the juice of aloe leaves are anthraquinones, acemannan, andprostaglandins. Chunks of aloe pulp are popular as beverages in Asia. Aloe has long been propagated by splitting its off-shoots, and this may account for its narrow genetic variations. In this research, genetic variations of A. vera and A. vera var. Chinensis, were induced by gamma irradiation. In vitro shoots of Aloe were irradiated with gamma ray at the dosage of 10-60 gy, then propagated on Murashige and Skoog (MS) solid medium containing 1 mg/l BAP. The results showed that shootlets of A. vera var. Chinensis were still alive up to 40 gy but the leaves became stiffer, while A. vera only tolerated irradiation up to 20gy. At 50-60 gy, all cultures died after 2 months. Visual observation on irradiated in vitro shoots showed that new variants appeared at the dosage of 20 gy, although in very low frequencies. Leaves became half green and half white in A. vera and white-green-white in A. vera var. Chinensis. Confirmation whether those variants were of genetic or morphological origin needs to be further investigated.